Tobacco cigarette smoking exacerbates aortic calcification in an early stage of myocardial infarction in a female mouse model. Issue 2 (16th July 2019) - Zalghout, Sara; Kaplan, Abdullah; Abidi, Emna; El‐Achkar, Ghewa A.; Nour‐Eldine, Wared; Khalil, Asmaa A.; Kobeissy, Firas; Husari, Ahmad; Habib, Aida; Zouein, Fouad A.; Hamade, Eva
Abstract: Despite increased social awareness, marketing restraints, tobacco taxation, and available smoking cessation rehab programs, active and passive smoking remain a worldwide challenging epidemic and a key risk factor for cardiovascular diseases development. Although cardiovascular (CV) protection is more pronounced in women than in men due to estrogenic effects, tobacco cigarette smoking exposure seems to alter this protection by modulating estrogen actions via undefined mechanisms. Premenopausal cigarette smoking women are at higher risk of adverse CV effects than non‐smokers. In this study, we investigated the impact of cigarette smoking on early CV injury after myocardial infarction (MI) in non‐menopausal female mice. Aortic arch calcification, fibrosis, reactive oxygen species, and gene expression of inflammatory and calcification genes were exaggerated in mice exposed to cigarette smoke (CS). These findings suggest that aortic injury following MI, characterized by vascular smooth muscle cells transdifferentiation, calcification, inflammation, and collagen deposition but not cardiac dysfunction is exacerbated with CS exposure. The novel findings of this study highlight the importance of aortic injury on short and long‐term prognosis in CS‐exposed MI females. Linking those findings to estrogen alteration is probable and entails investigation. Abstract : In summary, the current study demonstrates that tobacco cigarette smoking aggravates aortic injury and induces early calcification after myocardial infarction in young female mice and stresses the detrimental impact of cigarette smoking on the well‐known female cardiovascular protection.